Determinants of Firm Profitability: Evidences from Bangladeshi Manufacturing Industry - Sahabuddin, Mohammad; Synthia, Sabreena Khan (The Economics and Finance Letters, 2020)
This study aims to investigate the factors which have impact on profitability of the manufacturing firms of Bangladesh. The determinants are divided into three categories i.e. firm-specific, industry-specific and macroeconomic factors and the profitability of the firms is defined with return on assets (ROA). To investigate this relationship, the study has taken into consideration of 508 sample observations from 113 Bangladeshi listed manufacturing firms covering the year from 2014 to 2018. The model this study used, includes the dynamic aspect of profitability and thus a dynamic panel estimator i.e. the General Method of Moments (G.M.M.) was applied. The result of this study shows that firm-specific factors (age, labor cost), industry-specific factor (concentration) and macroeconomic factors (G.D.P. growth rate, inflation) have significant influence on manufacturing firm’s profitability.